2010
DOI: 10.1111/j.1467-9566.2009.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

The experience of infertility: a review of recent literature

Abstract: About 10 years ago Greil published a review and critique of the literature on the socio-psychological impact of infertility. He found at the time that most scholars treated infertility as a medical condition with psychological consequences rather than as a socially constructed reality. This article examines research published since the last review. More studies now place infertility within larger social contexts and social scientific frameworks although clinical emphases persist. Methodological problems remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
517
2
31

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 656 publications
(579 citation statements)
references
References 156 publications
(266 reference statements)
29
517
2
31
Order By: Relevance
“…We also acknowledge that most of this evidence has been derived from individuals seeking treatment and that it does not elucidate the experiences of people who do not 'define their [in]ability to have a child as a problem'. 3 The available evidence supports the assertion 83 that normative assumptions about the importance of child bearing and rearing for women coupled with the focus of ART treatment on women's bodies have reduced the visibility and awareness of men's experiences of childlessness. These data suggest that independent of their partner's wishes, fertile and infertile men want to father children and experience fatherhood.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…We also acknowledge that most of this evidence has been derived from individuals seeking treatment and that it does not elucidate the experiences of people who do not 'define their [in]ability to have a child as a problem'. 3 The available evidence supports the assertion 83 that normative assumptions about the importance of child bearing and rearing for women coupled with the focus of ART treatment on women's bodies have reduced the visibility and awareness of men's experiences of childlessness. These data suggest that independent of their partner's wishes, fertile and infertile men want to father children and experience fatherhood.…”
Section: Discussionmentioning
confidence: 49%
“…67,83 However, there is now a body of evidence that elucidates some of the psychological and social aspects of infertility for men. 3 While the research has been undertaken in diverse settings using varied designs, sampling and recruitment strategies, and data sources, there is considerable consistency among the findings. We acknowledge that in limiting the search to the English-language literature and including only studies with an identified focus on men that evidence relevant to this review might have been overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because there is mixed evidence regarding the causation (which member was diagnosed with infertility) and its relationship with psychological adjustment (see [41]) and discontinuation of treatment [21], two dummy variables were created to explore if female or male causation have different contributions to the decision of discontinuing treatments (presence of female causation versus others and presence of male causation versus others).…”
Section: Resultsmentioning
confidence: 99%
“…La incapacidad para tener hijos repercute en el bienestar de las personas y a su núcleo familiar, especialmente a las mujeres, ya que son las que sienten mayor presión social para convertirse en madres, suelen ser consideradas culpables por los fracasos reproductivos y son sus cuerpos los que deben soportar las intervenciones médicas y sus consecuencias 4,5 . En parte, este efecto negativo en las personas y en su entorno familiar es lo que llevó a la Organización Mundial de la Salud (OMS) junto a otras organizaciones, a definir la infertilidad como una enfermedad 1 .…”
unclassified